2015
DOI: 10.1088/0957-0233/26/10/105004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of asphere measurements by tactile and optical metrological instruments

Abstract: A comparison of topography measurements of aspherical surfaces was carried out by European metrology institutes, other research institutes and a company as part of an European metrology research project. In this paper the results of this comparison are presented. Two artefacts were circulated, a small polymer coated aspherical lens with a clear aperture of about 12 mm, and a large conical convex lens with a clear aperture of 300 mm developed for the ESO Very Large Telescope. The participating laboratories were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…In this situation, comparisons are a key factor in gaining new insights. Comparisons [6][7][8][9] have shown that, while some progress has been achieved, further improvements are also necessary. Most of the specimens used in these comparison studies were conventional spherical or aspherical surfaces made of glass.…”
Section: Introductionmentioning
confidence: 99%
“…In this situation, comparisons are a key factor in gaining new insights. Comparisons [6][7][8][9] have shown that, while some progress has been achieved, further improvements are also necessary. Most of the specimens used in these comparison studies were conventional spherical or aspherical surfaces made of glass.…”
Section: Introductionmentioning
confidence: 99%
“…The decreasing number of elitists would significantly speed up the convergence speed in the first stage of the iteration process with many elitists, and keep the exploitation ability in the later stage by removing the elitists for more potential trials. The elitists are selected by ascending order of fitness function evaluations and used in calculating the Mean i of TLBO in (21). This ETLBO makes it easy to achieve the desired searching results with low computational complexity.…”
Section: Elitist Strategymentioning
confidence: 99%
“…Among various surface fitting algorithms, the polynomial approximation is the most popular one. The desirable properties of Zernike polynomials, such as orthogonality, rotational symmetry, relation to classical Seidel aberrations, and simple representation, have made it the most popular basis function for analyzing optical surfaces [19][20][21]. Ares and Royo studied the fitting performance of Zernike polynomials, and found that low-degree Zernike polynomials are suitable for fitting simple wavefronts [22].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8]). Another attempt to compare different measurement principles was carried out in an EMRP project in 2015 [9]. However, the number of specimens and participants brought together in this study by CC UPOB e.V.…”
Section: Introductionmentioning
confidence: 99%